“Internationalists” and “Locals” in Research: Similar Productivity Patterns Across Europe - Kwiek, Marek (International Higher Education, 2015)
The article shows a high correlation between international collaboration in research and research productivity across eleven European systems and major academic disciplines. The data come from global CAP (The Changing Academic Profession) and European EUROAC (“The Academic Profession in Europe: Responses to Societal Challenges”) projects, and include 17,211 usable cases. Cross-national and cross-disciplinary differences are studied and groups of “internationals” and “locals” in research are contrasted.